A Ugi multicomponent reaction in the synthesis of N-cyclohexyl-2-(N-(4-methoxybenzyl)acetamido)-2-(thien-2’-yl)acetamide - Costa, Susana P. G. (2016)
The aim of this work is the synthesis of a protected unnatural amino acid using a Ugi multicomponent reaction, namely N-cyclohexyl-2-[N-(4-methoxybenzyl)acetamido]-2-(thien-2-yl)acetamide. Several experimental techniques will be considered such as thin-layer chromatography (TLC), vacuum filtration, and column chromatography on silica gel. The determination of the structure of the compound synthesized will be performed by NMR spectroscopy.